Two New Dihydrosphingosine Analogs Against Mycobacterium tuberculosis Affect gltA1, lprQ, and rpsO Expression - Peñuelas-Urquides, Katia; Bermúdez de León, Mario; Silva-Ramírez, Beatriz; Castorena-Torres, Fabiola; Molina-Salinas, Gloria María; Castro-Garza, Jorge; Becerril-Montes, Pola; del Olmo, Esther; San Feliciano, Arturo; González-Escalante, Laura Adiene; Villarreal-Treviño, Licet; Said-Fernández, Salvador (Frontiers in Microbiology, 2021)
The emergence of multidrug-resistant (MDR) Mycobacterium tuberculosis strains threaten the control of tuberculosis. New antitubercular dihydrosphingosine analogues, named UCIs, have been evaluated in preclinical studies but their cellular and molecular mechanisms of action against M. tuberculosis are still unknown. The aim of this study was to evaluate the effect of UCI exposure on gene expression of drug-sensitive H37Rv and MDR CIBIN:UMF:15:99 clones of M. tuberculosis which were isolated, phenotypically, and genetically characterized, cultured to log phase and treated with UCI compounds; followed by total RNA isolation, reverse transcription and hybridization assays on Affymetrix genomic microarrays. Data were validated with RT-qPCR assays. As results, UCI-05 and UCI-14 exposure increased gltA1 expression in drug-sensitive H37Rv clones. Furthermore, UCI-05 increased lprQ expression in MDR CIBIN:UMF:15:99 M. tuberculosis clones while UCI-14 reduced the expression of this gene in drug-sensitive H37Rv clones. In addition, UCI-05 reduced rpsO expression in drug-sensitive H37Rv clones. We found gene expression alterations that suggest these molecules may alter carbon and lipid metabolism as well as interfere in the protein-producing machinery in M. tuberculosis.